Kolaborasi Pemerintah Desa dan Lembaga Adat dalam Pelestarian Budaya Lokal di Desa Kuntu Kecamatan Kampar Kiri - Adni Fazila; Fitria Ramadhani Agusti Nst (Yayasan Almanar Pujud, 2025)
This study aims to determine the collaboration between the village government and traditional institutions in preserving local culture in Kuntu Village, Kampar Kiri District. The research method used is descriptive qualitative through observation, interviews, and documentation. The results of the study indicate that the collaboration of the village government and traditional institutions in preserving local culture in Kuntu Village, Kampar Kiri District has been running but has not been optimal. Seen from several indicators 1) Face to face dialogue, 2) Building trust (Trust Building), 3) Commitment to the process (Commitment to process), 4) Sharing understanding and experience (Share Understanding), 5) Interim results that can be utilized (Outcome). The inhibiting factors are 1) Minimal participation of the younger generation due to the influence of modern lifestyles and lack of interest in traditional activities. 2) Lack of socialization and promotion. 3) Supporting infrastructure for cultural activities and Budget limitations. 4) Shifting values ​​and changes in people's mindsets towards tradition. 5) Lack of Participation of the Driving Team, and 6) Low communication and coordination between the Village Government and Traditional Institutions are obstacles to cultural preservation.